In Silico Evaluation of Bioactive Compounds from Artocarpus heterophyllus Leaves as Potential Aromatase Inhibitors for Estrogen Receptor Positive Breast Cancer - Ihya Zakira Sani,; Afif, Iffat Syafiqoh; Azril, Azril; Purnamasari , Devi; Bisra, Marido (SAINSTEK International Journal on Applied Science, Advanced Technology and Informatics, 2025)
Breast cancer remains one of the leading causes of mortality among women worldwide, particularly estrogen receptor positive subtypes that depend on aromatase (CYP19A1) activity for estrogen biosynthesis. This study aims to evaluate phytochemical compounds isolated from Artocarpus heterophyllus leaves as potential natural aromatase inhibitors using an integrated in silico approach. A total of ten reported secondary metabolites were analyzed alongside Letrozole as a reference inhibitor. Molecular docking was performed against human aromatase (PDB ID: 4GL7) using MOE 2019, and protocol validation was confirmed by redocking of the native ligand with RMSD values below 2.0 Å. The results show that 3 prenyl luteolin, prenyl caffeate, and artocarpanone exhibited strong binding affinities of -7.7958, -7.0193, and -6.9688 kcal/mol, respectively, exceeding that of Letrozole (-6.8069 kcal/mol), with stable docking conformations. Drug likeness evaluation indicates that all tested compounds comply with Lipinski and Veber rules, present acceptable polar surface area, limited rotatable bonds, and a bioavailability score of 0.55. ADMET prediction reveals high gastrointestinal absorption, moderate distribution, controlled clearance, and low toxicity risk, with no predicted AMES mutagenicity or hepatotoxicity for most compounds. These findings suggest that A. heterophyllus contains promising bioactive metabolites with favorable binding characteristics and pharmacokinetic profiles, supporting their potential as lead candidates for the development of safer, plant derived aromatase inhibitors for estrogen dependent breast cancer therapy.